Temporal Conjunctions and Their Semantic Extensions: The Case of kî in Biblical Hebrew - Locatell, Christian S. (Journal of Semitic studies, 2020)
Past analyses of kî have tended toward descriptive taxonomies or proposals of a highly abstract semantic core. Taxonomic approaches have the strength of descriptive rigour while proposals of an abstract core have the strength of offering a coherent analysis of its various uses. However, the former offer little or no explanation for the semantic variation of kî⁠, and the latter simply attribute such variation to context. This paper argues that the best analysis of kî (or any such polysemous word) will both account for real variation in meaning without simply attributing it to context, and will also explain the principled connection between seemingly unrelated uses. Utilizing insights from cognitive semantics and grammaticalization theory, this paper will argue that temporal kî spans an internally complex semantic category, the various points of which served as the source for semantic extensions into its causal and conditional uses.